Simultaneous induction of anthocyanin and peroxidase by sucrose in hypocotyls and roots of Chinese red radish seedlings - L. WANG; X.-X. JING; P.-P. ZHAO; L.-F. WANG; Y. YIN; Y.-F. LI (Biologia Plantarum, 2020)
Anthocyanin and peroxidase (POD) are important active compounds in Chinese red radish (Raphanus sativus L.). The effects of exogenous sucrose, mixture of fructose and glucose (F/G 1:1), and mannose on anthocyanin accumulation and POD activity were investigated in hypocotyls and roots of red radish seedlings. Sucrose was most effective in inducing anthocyanin accumulation and POD activity in both organs, followed by F/G; mannose caused only a little increase of anthocyanin content and POD activity in hypocotyls, but a decrease in roots. The distribution of anthocyanin accumulation was different between hypocotyls and roots in the presence or absence of sucrose. Anthocyanin was clearly induced in root tips and cortex under exogenous sucrose. Accumulation of anthocyanin was closely correlated to the increase of endogenous sucrose content rather than glucose or fructose content. Sucrose significantly induced the expressions of late anthocyanin biosynthetic genes by up-regulating Raphanus sativus myeloblastosis 1 and Raphanus sativus transparent testa 8 in both organs. The POD activity significantly increased following the remarkable accumulation of anthocyanin in hypocotyls under exogenous sucrose, which may be partially required for anthocyanin oxidation. In roots, the high POD activity might lead to a low anthocyanin content by degrading anthocyanin and diverting the metabolic flux to lignin synthesis.